2017
DOI: 10.21632/irjbs.10.1.57-68
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Innovation and Entrepreneurial Self-Efficacy to Digital Startup Success

Abstract: Establishing and developing a startup business is not easy. Startup success depend on various aspects, such as financial,business model, and learning organizations. Personalities factor of founders have a contribution in business development, especially entrepreneurial self-efficacy (ESE) and innovation. But, in Indonesia, there is still no psychological study who see the contribution of those factors on business success in digital startup. This study aimed to understand how both factors influence startup digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…Moreover, since these dimensions are task-specific, consideration both of individual characteristics such as personality and of interaction with environmental forces is essential in executing entrepreneurial actions (Chen et al, 1998). Among the authors who have considered the linkage between ESE and firm performance, growth and renewal are considered by Bratkovic et al (2012), Hmieleski and Baron (2008), and Dessyana and Riyanti (2017), who confirmed that the higher the degree of ESE, the higher the chances of success in the business start-up. However, limited attention has been paid to the relation more specifically between ESE and business tech start-up.…”
Section: Ese and Business Tech Start-upmentioning
confidence: 99%
“…Moreover, since these dimensions are task-specific, consideration both of individual characteristics such as personality and of interaction with environmental forces is essential in executing entrepreneurial actions (Chen et al, 1998). Among the authors who have considered the linkage between ESE and firm performance, growth and renewal are considered by Bratkovic et al (2012), Hmieleski and Baron (2008), and Dessyana and Riyanti (2017), who confirmed that the higher the degree of ESE, the higher the chances of success in the business start-up. However, limited attention has been paid to the relation more specifically between ESE and business tech start-up.…”
Section: Ese and Business Tech Start-upmentioning
confidence: 99%
“…However, these aspects fall outside our scope and represent complementary Complexity viewpoint, with their own peculiarities and interpretation difficulties, in characterizing the startup system. In conclusion, the choice to consider successful firms according to collected funds yields is twofold: (i) it is intuitive and (ii) widespread in economic literature [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the ideas of network success theory [21], we investigate the relation between the success of a startup, which a large body of literature defines as the capability of obtaining massive capital [22], and its capability to fully exploit its own business network. Actually, this attitude could shed light on complex economic dynamics [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The higher the self-efficacy of selfemployment the higher the success for start-up business. Innovation plays a role in the early phases of entrepreneurship development (3 months -2 years) [21]. Creativity affects one's entrepreneurial intentions.…”
Section: Content-based Digital Productsmentioning
confidence: 99%